DEVELOPMENT OF STUDENT WORK SHEETS BASED ON INDIGENOUS KNOWLEDGE - Azizahwati Azizahwati; Ruhizan Mohd Yasin (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2017)
This study aims to develop an indigenous knwledge-based student worksheets for valid Grade VII junior high school students. This research uses Research and Development (R & D) method with reference to model 4_D. The instruments used are LKS validation sheets and user response questionnaires from teachers and students. The research that has been carried out concludes: the quality of the developed LKS scores with high category as well as the user response from very high teachers and from the high categorized students so it is good to use.